Peran Media Sosial Tiktok dan Kredibilitas Influencer Terhadap Keputusan Pembelian Melalui Ekuitas Merek Pada Produk Erigo - Fauzi Dermawan Tutupoho; Ferryal Abadi (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2024)
This research explores the influence of social media, influencer credibility, and brand equity on the purchasing decisions of Erigo products. The study population consists of active TikTok users who are students at Esa Unggul University and are buyers of Erigo products. In this research, data were collected from 105 respondents who met these criteria. The research methodology is non-experimental quantitative with a descriptive approach and utilizes correlation methods to analyze the relationships between variables. The analysis results indicate that brand equity has a significant positive influence on purchasing decisions. Although influencer credibility contributes positively to brand equity, its impact is not significant on purchasing decisions. Meanwhile, social media significantly influences brand equity and purchasing decisions. The implications of these findings provide strategic insights into the marketing development of Erigo products, focusing on optimizing social media and strengthening consumer trust through collaborations with influencers.